Meningkatkan Kesadaran Masyarakat tentang Imunisasi melalui Edukasi Door to Door di Desa Mukhan, Kecamatan Indrajaya, Kabupaten Aceh Jaya - Fildzah Maulida Maghfirah; Elen Felensia Br Brutu; Elda Zianyu Safani; Kharisma Yanti Murnia; Sari Ayu (Antigen : Jurnal Kesehatan Masyarakat dan Ilmu Gizi, 2025)
The coverage of complete basic immunization (CBI) in Indonesia has experienced a significant decline, dropping from 93.7% in 2019 to 84.5% in 2021. Aceh Province was recorded as one of the lowest regions nationwide, achieving only 39.4% and ranking among the bottom three provinces. Low public awareness and knowledge, particularly in rural areas, have become the main factors contributing to the low participation in immunization programs. This study aimed to evaluate the effectiveness of door-to-door education in improving the knowledge and awareness of mothers with toddlers and its impact on immunization participation in Mukhan Village, Indrajaya Subdistrict, Aceh Jaya District. The research applied a quasi-experimental method with a pre-test design and no control group, involving 25 mothers of toddlers who were directly visited through a one-month door-to-door program. Data were collected using structured questionnaires and by recording the immunization status of the toddlers. The findings revealed that before the intervention, only 36% of toddlers had received complete basic immunization, while 64% had incomplete immunization. After the educational intervention, there was a positive shift in attitudes among several mothers who had previously doubted or refused immunization, including one mother who later agreed to participate in catch-up immunization. Door-to-door education proved effective in enhancing knowledge and awareness, as it enabled direct communication that clarified myths and addressed concerns about immunization. Although overall immunization coverage remains low, the observed positive change in attitudes highlights the potential for increased participation through continuous efforts, multi-stakeholder collaboration, and the active involvement of health cadres and local community leaders.